Enterprise Microservices: Revolutionizing Telecom Network Architecture - Bhaskara Srinivas Beeraka (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of enterprise microservices architecture in the telecommunications industry through the implementation of the UltraVailable Network Service (UVNS) project. The article examines how microservices address challenges related to critical network scalability, availability, and operational efficiency. The article demonstrates the significant advantages of microservices over traditional monolithic architectures through a detailed analysis of automated provisioning, billing systems, and advanced monitoring capabilities. The implementation showcases innovations in dynamic resource allocation, high availability features, and data management systems supported by artificial intelligence and machine learning technologies. The results reveal substantial improvements in service delivery, operational costs, and system performance, establishing a new benchmark for telecommunications infrastructure management.